2016
DOI: 10.3390/molecules21030367
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetics of Maleic Acid as a Food Adulterant Determined by Microdialysis in Rat Blood and Kidney Cortex

Abstract: Maleic acid has been shown to be used as a food adulterant in the production of modified starch by the Taiwan Food and Drug Administration. Due to the potential toxicity of maleic acid to the kidneys, this study aimed to develop an analytical method to investigate the pharmacokinetics of maleic acid in rat blood and kidney cortex. Multiple microdialysis probes were simultaneously inserted into the jugular vein and the kidney cortex for sampling after maleic acid administration (10 or 30 mg/kg, i.v., respective… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 24 publications
1
2
0
Order By: Relevance
“…Our targeted analysis revealed that significantly elevated urinary levels of 8-OHdG and 8-NO 2 Gua were observed as early as within 12 hours after MA consumption; while statistically meaningful increases in 8-isoPGF 2 α were witnessed within 24 hours. Both phenomena correspond with the rapid absorption and elimination of MA demonstrated in established reports (Hou, Lu, Lin, Lin, & Tsai, 2016;Wu et al, 2016a). Additionally, our results revealed that MA triggers oxidant and nitrosant attacks; such stress could lead to cellular or tissue damage in the kidneys and liver, as supported by our histological observations of undefined glomerular cells, disorderly arrangement of the tubular epithelial cell vacuoles and renal tubules.…”
Section: Oxidative Stress Inflammation and Lipid Peroxidationsupporting
confidence: 89%
“…Our targeted analysis revealed that significantly elevated urinary levels of 8-OHdG and 8-NO 2 Gua were observed as early as within 12 hours after MA consumption; while statistically meaningful increases in 8-isoPGF 2 α were witnessed within 24 hours. Both phenomena correspond with the rapid absorption and elimination of MA demonstrated in established reports (Hou, Lu, Lin, Lin, & Tsai, 2016;Wu et al, 2016a). Additionally, our results revealed that MA triggers oxidant and nitrosant attacks; such stress could lead to cellular or tissue damage in the kidneys and liver, as supported by our histological observations of undefined glomerular cells, disorderly arrangement of the tubular epithelial cell vacuoles and renal tubules.…”
Section: Oxidative Stress Inflammation and Lipid Peroxidationsupporting
confidence: 89%
“…To achieve detection of low concentrations of MA, advances in analytical methods with LC-MS/MS and Near-Infrared (NIR) spectroscopy and chemometrics were reached to attain high sensitivity and specificity [ 6 , 7 ]. Improvements in these methods furthered our understanding of the pharmacokinetic behavior and can also assist in investigating the toxicological implications of MA from consumption [ 8 10 ]. However, most of the toxic effects occur at the cellular and tissue levels.…”
Section: Introductionmentioning
confidence: 99%
“…The MD probe recovery could be influenced by the following experimental elements including the length, diameter and materials of the membrane, effective surface area, probe geometry, the diffusion coefficient of the analyte, the component of perfusion solution, the flow rate for perfusion, time, temperature, and the property of the substance. For MD in vivo, the tissue environment has additional effects on the recovery (Sun et al, 2001;Hou et al, 2016). In the present study, MD was successfully conducted for the measurement of NAG in blood as well as brain tissue.…”
Section: Discussionmentioning
confidence: 97%